2007
DOI: 10.1111/j.1468-2982.2007.01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Mechanisms of Controlled-Release Metoprolol in Migraine: A Double-Blind, Placebo-Controlled Study

Abstract: beta-Blockers are widely used in the prophylaxis of migraine and have been described as very effective drugs in many studies. Some investigators have demonstrated that the clinical improvement of migraine corresponds to the normalization of the contingent negative variation (CNV), a slow cortical potential measuring cortical information processing. However, most of these studies have contained a variety of methodological pitfalls, which we attempted to address in the current study. Twenty patients suffering fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…35 The second study (smaller, underpowered; n ϭ 25) found cyclandelate significantly reduced the number of migraine days and duration (assessed using a contingent negative variation measure). 36 Conclusions. The efficacy of cyclandelate is unknown (conflicting Class II studies).…”
mentioning
confidence: 99%
“…35 The second study (smaller, underpowered; n ϭ 25) found cyclandelate significantly reduced the number of migraine days and duration (assessed using a contingent negative variation measure). 36 Conclusions. The efficacy of cyclandelate is unknown (conflicting Class II studies).…”
mentioning
confidence: 99%
“…Reports are available regarding the lack of normalizing effect on CNV abnormal pattern with flunarizine Bussone et al, 1985], nifedipine [Diener et al, 1989], or riboflavin [Sndor et al, 2000]. Cyclandelate, a calcium antagonist with anti-5HT properties, reduced CNV amplitude in migraineurs, without recovery of normal habituation [Siniatchkin et al, 1998] (Table 1).…”
Section: Effects Of Preventive Agents On Interictal Neurophysiologic mentioning
confidence: 97%
“…Thus, there is evidence of cortical hyperexcitability and lack of habituation to repetitive stimuli in the migraine brain. Furthermore, this phenomenon can be normalised by treatment with beta-blockers, calcium channel blockers, aspirin and 5-HT 1 receptor agonists that show anti-migraine efficacy [174]. Similarly, hyperexcitability in the occipital cortex has also been demonstrated in migraine [10].…”
Section: Central Sensitizationmentioning
confidence: 99%